The Influence of Competence and Discipline on Employee Performance - Rustandi, Rahmat (Greenation International Journal of Economics and Accounting, 2025)
The purpose of this research is to determine and analyze: (1) Competence; (2) Work Discipline; (3) Performance; and (4) The Influence of Competence and Work Discipline on Employee Performance at the X Office in West Java Province, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at Department X in West Java Province, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the Employee Competence at Dinas X in West Java Province received mostly positive responses from the Employees; the work discipline of Employees at Dinas X in West Java Province can generally be considered good, and the Employee Performance at Dinas X in West Java Province is currently rated as good. Competence and work discipline simultaneously influence Employee Performance at Dinas X in West Java Province. However, partially, Competence has a dominant influence on Employee Performance compared to Work Discipline. Because competence has a more dominant influence on performance, it becomes the top priority in improving employee performance. therefore, the X Office in West Java Province is expected to improve the competence of employees at the X Office in West Java Province by involving them in training and education, so that they can work more professionally.